Silicon Nitride Substrate
By orienting β-Si3N4 grains in the thickness direction through controlled sintering aid volatilization, the silicon nitride substrate achieves enhanced thermal conductivity and mechanical strength, addressing heat dissipation limitations in semiconductor circuit boards.
Patent Information
- Application Number
- JP2023221990
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-29
- Filing Date
- 2023-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-04-13
AI Technical Summary
Silicon nitride substrates exhibit lower thermal conductivity compared to aluminum nitride substrates, limiting their ability to efficiently dissipate heat generated by semiconductor chips, thereby restricting the power input to semiconductor circuit boards.
A silicon nitride substrate is produced with controlled volatilization of a sintering aid during the nitriding and sintering process, orienting β-Si3N4 grains in the thickness direction, enhancing thermal conductivity to 80-93 W/m K and maintaining sufficient mechanical strength through controlled orientation of β-Si3N4 grains.
The substrate effectively dissipates heat from semiconductor chips to a heat sink, allowing for increased power input to the circuit board while maintaining mechanical integrity, suitable for various semiconductor applications.
Smart Images

Figure 0007660654000002 
Figure 0007660654000003 
Figure 0007660654000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon nitride substrate having excellent thermal conductivity in the thickness direction and a method for manufacturing the same. do. [Background technology]
[0002] In recent years, silicon nitride (Si3N4) substrates have been applied to semiconductor circuit boards such as power semiconductors. As semiconductor circuit boards, alumina (Al2O3) substrates and aluminum nitride substrates are being used. An alumina (AlN) substrate is used. The thermal conductivity of an alumina substrate is about 30 W / m K. However, it is possible to reduce costs. In addition, the thermal conductivity of aluminum nitride substrates is 160W. / m·K or higher. On the other hand, silicon nitride substrates have a thermal conductivity of Substrates with a resistance of 50 W / m·K or higher have been developed.
[0003] Silicon nitride substrates have a lower thermal conductivity than aluminum nitride substrates, but have a higher three-point bending strength. The three-point bending strength of aluminum nitride substrate is usually 300-400 MPa. The strength of the material is about 100 MPa, and the strength tends to decrease as the thermal conductivity increases. By taking advantage of this point, the silicon nitride substrate can be made thinner. This allows the temperature to be lowered, improving heat dissipation.
[0004] Taking advantage of these characteristics, silicon nitride substrates can be used as circuit boards by attaching circuit parts such as metal plates. In addition, the pamphlet of International Publication No. WO2011 / 010597 There is also a method of using it as a circuit board for a pressure-welded structure as shown in (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. WO2011 / 010597 Brochure Summary of the Invention [Problem to be solved by the invention]
[0006] However, as mentioned above, silicon nitride substrates have a lower thermal conductivity than aluminum nitride etc. When used in semiconductor circuit boards, it absorbs heat generated by semiconductor chips into a heat sink due to its low thermal conductivity. This meant that the power that could be input to the semiconductor circuit board could not be efficiently dissipated to the semiconductor circuit board. Therefore, silicon nitride substrates are required to have higher thermal conductivity, especially in the thickness direction. It is being done.
[0007] An object of the present invention is to provide a silicon nitride substrate having excellent thermal conductivity in the thickness direction. do. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention provides a silicon nitride substrate having an X-ray diffraction peak of β-Si3N4 when the substrate surface is irradiated with X-rays, and an orientation degree fa indicating the ratio of the major axis (c-axis) of β-Si3N4 grains oriented in the thickness direction in the silicon nitride substrate. 0.0144 ~ 0.2202 is included in the range of When a test piece of 4 mm × 35 mm is bent from the midpoint of two supports with a distance of 30 mm between the two supports, the average value of the three-point bending strength of 10 test pieces is in the range of 806 to 872 MPa; Thermal conductivity in the thickness direction is Range: 80~93.0W / m K The present invention relates to a silicon nitride substrate, characterized in that:
[0009] fa = (P - P0) / (1 - P0) ... (1).
[0010] In formula (1), P is represented by formula (2), and the (10° ≦2θ≦80°), all X-ray diffraction line intensity ratios related to the c-axis (specifically (101 ) surface, (111) surface, (201) surface, (121) surface, (301) surface, (221) surface, (1 31), (002), (401), (102), (112), (231), X-ray diffraction of (202), (141), (212), (302), (501) The strength of the powder is the object of the present invention. P0 is expressed by the formula (3), and in the case of β-type silicon nitride powder (10°≦2θ≦ 80°), all X-ray diffraction line intensity ratios related to the c-axis (specifically, the (101) plane, ( 111), (201), (121), (301), (221), (131) , (002), (401), (102), (112), (231), (202 ), (141), (212), (302), and (501) planes. It means elephant.
[0011] P=(I(101)+I(111)+I(201)+I(121)+I(301)+I (221)+I(131)+I(002)+I(401)+I(102)+I(112) +I(231)+I(202)+I(141)+I(212)+I(302)+I(50 1)) / (I(100)+I(110)+I(200)+I(101)+I(120)+ I(111)+I(300)+I(201)+I(220)+I(121)+I(130 )+I(301)+I(400)+I(221)+I(131)+I(230)+I(0 02)+I(140)+I(401)+I(102)+I(112)+I(231)+I (202)+I(500)+I(141)+I(330)+I(212)+I(240) +I(302)+I(501))‥(2).
[0012] P0=(I0(101)+I0(111)+I0(201)+I0(121)+I0( 301)+I0(221)+I0(131)+I0(002)+I0(401)+I0( 102)+I0(112)+I0(231)+I0(202)+I0(141)+I0( 212)+I0(302)+I0(501)) / (I0(100)+I0(110)+I 0(200)+I0(101)+I0(120)+I0(111)+I0(300)+I 0(201)+I0(220)+I0(121)+I0(130)+I0(301)+I 0(400)+I0(221)+I0(131)+I0(230)+I0(002)+I 0(140)+I0(401)+I0(102)+I0(112)+I0(231)+I 0(202)+I0(500)+I0(141)+I0(330)+I0(212)+I 0(240)+I0(302)+I0(501))‥(3).
[0013] The present invention also provides a process for preparing a slurry by mixing silicon powder, a sintering aid, and a dispersion medium. forming a sheet from the slurry; and heating the sheet in a nitrogen-containing atmosphere. a step of treating the silicon in the sheet body to nitride it and form silicon nitride; and a step of sintering the sheet body containing the above-mentioned, to produce a silicon nitride substrate. In the step of forming the silicon nitride, the volatilization of the sintering aid is controlled and the direction of movement of the sintering aid is controlled. A method for producing a silicon nitride substrate, characterized in that silicon nitride particles are oriented in the thickness direction. Regarding the law.
[0014] According to the present invention, silicon is converted into silicon nitride through a nitriding process, and then into silicon nitride through a sintering process. When obtaining the substrate, at least when obtaining silicon nitride, the volatilization of the sintering aid is promoted. Therefore, due to the volatilization of the sintering aid, the generated silicon nitride β particles move in the thickness direction. The electrons become oriented in the direction perpendicular to the surface.
[0015] As a result, when the substrate surface was irradiated with X-rays, the silicon nitride substrate had an X-ray diffraction peak of β-Si3N4, and the degree of orientation fa, which indicates the proportion of the long axis (c-axis) of the β-Si3N4 grains oriented in the thickness direction, was 0.0144 ~ 0.2202 Range The three-point bending strength when a 4 mm x 35 mm test piece is bent from the midpoint of the two supports with a distance of 30 mm between the two supports is within the range of 806 to 872 MPa. The silicon nitride substrate has a thermal conductivity in the thickness direction of Range: 80~93.0W / m K Therefore, it has a higher thermal conductivity than the conventional silicon nitride substrate. This also makes it possible to obtain a silicon nitride substrate having sufficient strength for practical use.
[0016] Therefore, when used in semiconductor circuit boards, the heat generated by the semiconductor chips can be effectively absorbed by the heat sink. This allows the power to be efficiently released to the inverter, thereby increasing the power that can be input to the semiconductor circuit board. In other words, the excellent strength of the silicon nitride substrate makes it possible to manufacture power semiconductors and other semiconductor devices. The present invention can be applied to various semiconductor circuit boards.
[0017] In the silicon nitride substrate and the method for producing the same of the present invention, the sintering aid is a rare earth oxide and It is preferable that the magnesium compound is at least one of the above-mentioned compounds. Since the movement of the liquid phase generated from the binder in the thickness direction is promoted, the above-mentioned effects are more pronounced. It can be performed by author.
[0019] Furthermore, in the silicon nitride substrate of the present invention, the size of the main surface is 400 to 40,000 mm2. The density is 3.15 to 3.40 g / cm3, and the dielectric strength is 20 kV / mm or more. In this case, it is possible to obtain a silicon nitride substrate having a practically sufficient dielectric strength. . Effect of the Invention
[0020] As described above, according to the present invention, a silicon nitride based semiconductor device having excellent thermal conductivity in the thickness direction is provided. A plate can be provided. [Brief description of the drawings]
[0021] [Figure 1] 1 is a schematic diagram showing the crystal system of β-Si3N4. [Diagram 2] 1 is a schematic cross-sectional view of a silicon nitride substrate according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] FIG. 1 is a schematic diagram showing the crystal system of β-Si3N4, and FIG. FIG. 2 is a schematic cross-sectional view of a silicon nitride substrate in accordance with the present invention.
[0023] The silicon nitride substrate of the present invention preferably has a silicon nitride content of 85 mass% or more, More preferably, it is 87 mass % or more. As a result, as described below, silicon nitride Due to the crystal system (crystal structure) of the silicon nitride substrate, the thermal conductivity in the thickness direction is improved. If the content of silicon nitride is less than 85 mass %, the proportion of silicon nitride is small. Therefore, the improvement in thermal conductivity in the thickness direction of the silicon nitride substrate becomes insufficient.
[0024] The silicon nitride content is preferably 95 mass% or less, and more preferably 93 mass% or less. If the silicon nitride content exceeds 95 mass%, the silicon nitride substrate The amount of liquid phase is reduced due to the decrease in the content of sintering aid, and the vertical direction toward the separating agent layer is increased. Since the movement of the liquid phase is reduced, the silicon nitride formed is oriented in the thickness direction of the silicon nitride substrate. This makes it difficult to improve the thermal conductivity in the thickness direction of the silicon nitride substrate.
[0025] In the silicon nitride substrate of the present invention, the content of the sintering aid is preferably 5 mass % or more. The sintering aid is contained in an amount of 5 mass% or more, and more preferably 7 mass% or more. As described below, the liquid phase ratio is optimized when sintering a silicon nitride substrate to produce it. The silicon nitride particles are oriented perpendicular to the thickness direction, and the proportion of silicon nitride is optimized. The thermal conductivity of the silicon nitride substrate in the thickness direction is improved.
[0026] On the other hand, in the silicon nitride substrate of the present invention, the content of the sintering aid is 15 mass % or less. If the sintering aid content exceeds 15 mass%, the proportion of silicon nitride decreases. Therefore, the thermal conductivity of the silicon nitride substrate in the thickness direction, which is derived from silicon nitride, decreases.
[0027] In addition to the silicon nitride and sintering aids described above, the silicon nitride substrate of the present invention inevitably contains Including impurities. The unavoidable impurities are, for example, dispersions used in the manufacturing process of silicon nitride substrates. These include organic solvents as solvents, and additives such as binders and plasticizers.
[0028] When the surface of the silicon nitride substrate of the present invention is irradiated with X-rays, the X-ray diffraction peak of β-Si3N4 The long axis (c-axis) of the β-Si3N4 grains oriented in the thickness direction of the silicon nitride substrate The degree of orientation fa, which indicates the ratio of the orientation of the particles, is preferably in the range of 0 to 0.3.
[0029] As shown in Figure 1, the crystal system (crystal structure) of β-Si3N4 consists of (200) and (1 It has a hexagonal column shape with multiple faces, including (20) faces, on its side surfaces and (002) faces on its end surfaces. Therefore, when the substrate surface is irradiated with X-rays, the β-S oriented in the thickness direction of the silicon nitride substrate is The degree of orientation fa, which indicates the proportion of i3N4 particles, is in the range of 0 to 0.3, which means that silicon nitride In the thickness direction of the substrate, the β-Si3N4 grains are preferentially oriented, resulting in the morphology shown in Figure 2. In the silicon nitride substrate 10, most of the columnar β-Si3N4 particles 11 are oriented in the thickness direction. It should be noted that reference numeral 12 indicates a grain boundary phase resulting from a sintering aid or the like.
[0030] Inherently, the thermal conductivity of silicon nitride particles is higher in the length direction of the hexagonal column than in other directions. That is, in the present invention, as shown in FIG. 2, for example, silicon nitride (β- The proportion of Si3N4) oriented along the thickness direction of the silicon nitride substrate increases. The present invention can exhibit high thermal conductivity in the thickness direction.
[0031] In addition, the orientation indicates the ratio of β-Si3N4 grains oriented in the thickness direction in a silicon nitride substrate. When the degree fa is less than 0, i.e., in the negative range, the orientation in the plane direction becomes strong, and the above-mentioned action and effect are not obtained. Therefore, it is difficult to obtain a high thermal conductivity in the thickness direction of the silicon nitride substrate. In addition, the upper limit of the degree of orientation fa is currently 0.3, but from the viewpoint of thermal conductivity, this is too high. However, if this ratio is too high, the breaking strength in the thickness direction and the like may decrease. The mechanical strength of the material decreases.
[0032] In the silicon nitride substrate of the present invention, the thermal conductivity in the thickness direction is 80 W / m K or more, The preferable range is 85 W / m·K or more. This makes it possible to form the silicon nitride substrate of the present invention into a semiconductor circuit. When used on a printed circuit board, it efficiently dissipates heat generated by semiconductor chips to a heat sink. This makes it possible to increase the power that can be input to the semiconductor circuit board. That is, the excellent strength of the silicon nitride substrate makes it suitable for use in various semiconductor circuits, including power semiconductors. It can be applied to a substrate.
[0033] The above thermal conductivity is determined when the silicon nitride substrate of the present invention contains the above-mentioned silicon nitride and sintering aid. It can be obtained by satisfying the requirements of the amount and X-ray diffraction.
[0034] In addition, the silicon nitride substrate of the present invention has a flexural strength of 500 MPa or more according to the three-point method. The thickness is preferably 0.1 to 1.2 mm. This provides sufficient strength for practical use. As shown in Table 1 below, the silicon nitride substrate of the present invention can be obtained. The substrate has a flexural strength of 650 MPa or more, preferably 700 MPa, as measured by the three-point method. It may have a or more.
[0035] Furthermore, in the silicon nitride substrate of the present invention, the size of the main surface is 400 to 40,000 mm2. The density is 3.15 to 3.40 g / cm3, and the dielectric strength is 20 kV / mm or more. In this case, it is possible to obtain a silicon nitride substrate having a practically sufficient dielectric strength. .
[0036] Next, a method for producing the silicon nitride substrate of the present invention will be described.
[0037] First, silicon powder and sintering aid powder are prepared as raw materials. It is preferable that the diameter D50 of the impurity layer is 50 μm or less and the impurity oxygen content is 0.6 mass % or less. The amount of the sintering aid is preferably 15 parts by mass per 100 parts by mass of silicon powder. preferable.
[0038] The sintering aid is preferably a metal compound powder having a median diameter D50 of 10 μm or less. Metal compound powders include rare earth elements, magnesium, titanium, hafnium, etc. Among them, rare earth element oxides and magnesium compounds (magnesium compounds) are more preferable. These sintering aids have excellent fluidity and exhibit the following fluid behavior: This makes it easier to orient the silicon nitride particles in the thickness direction.
[0039] Next, a dispersion medium is added to the silicon powder and sintering aid, and the mixture is mixed with media in a ball mill, for example. The mixture is dispersed, crushed and mixed to prepare a slurry. The dispersion medium is toluene, ethanol, butadiene, etc. An organic solvent such as alcohol can be used.
[0040] Next, a binder, a plasticizer, etc. are added to the above slurry as necessary, and further The viscosity of the slurry is adjusted by vacuum degassing. Organic binders such as polyvinyl butyral and polymethyl methacrylate can be used. can.
[0041] Next, the viscosity-adjusted slurry is molded into a sheet by a doctor blade method, a roll method, or the like. The mixture is then molded into a sheet having a thickness of, for example, 0.2 to 1.5 mm. The sheet body is formed, for example, by applying a slurry onto a film, and then removing the film after drying. It is obtained by removing
[0042] Next, as necessary, a layer of ceramic powder and a dispersion medium is applied to the main surface of the sheet body. The slurry is applied to form a separating agent layer. As the dispersion medium, toluene, ethanol, etc. are used as the dispersion medium. The organic solvent used may be ethanol, butanol, or the like. Methods that can be used include plating, bar coating, screen printing, and the like.
[0043] Next, the sheet body is degreased as necessary, for example, in a non-oxidizing atmosphere at a temperature of 600° C. or less. After that, the sheet body is heated in a nitrogen-containing atmosphere at a temperature of 1200 to 1500°C. The silicon that constitutes the sheet is nitrided by holding it at 350° C. for 2 to 8 hours. The nitrogen partial pressure in the nitrogen-containing atmosphere is, for example, 0.05 to 0.5 MPa.
[0044] Next, the mixture is kept at a temperature of 1800 to 1950°C for 6 to 24 hours in a nitrogen-containing atmosphere. This causes sintering of silicon nitride.
[0045] In the present invention, a weight plate is used in the nitriding sintering process. (1) When nitriding silicon, A method in which the weight plate is not used and the upper surface is left free, and the weight plate is used only during sintering. (2) Using a porous plate as a weight plate, the silicon is nitrided and the silicon nitride is sintered and molded continuously. (3) A method of applying a load to the compact, or a method of using a dense plate as a weight to press the compact against the dense plate. One method is to provide a separating agent layer between the two.
[0046] The separation layer is made of ceramic powder and is thermally stable during nitriding and sintering. There are no particular limitations on the material as long as the dense plate can be separated after sintering is completed. Boron oxide is preferred.
[0047] In addition, if boron nitride is used as the ceramic powder, its purity must be 95% or more. The average particle size is preferably 5 to 20 μm. It is preferable that the thickness is 10 to 60 μm, or 20 to 60 μm.
[0048] A plurality of sheet bodies each having a separating agent layer formed on a main surface thereof are laminated with the separating agent layer interposed therebetween. In this case, a plurality of silicon nitride particles can be obtained by the above-mentioned nitriding and sintering steps. The substrates can be fabricated simultaneously.
[0049] As a result, when the substrate surface was irradiated with X-rays, it had an X-ray diffraction peak of β-Si3N4, The ratio of the long axis (c-axis) of β-Si3N4 grains oriented in the thickness direction in the silicon nitride substrate is shown. This makes it possible to obtain a silicon nitride substrate having a degree of orientation fa in the range of 0 to 0.3.
[0050] (Example)
[0051] Example 1 Metallic silicon powder and sintering aids (rare earth oxides and magnesium compounds), dispersants (Polymer The dispersion medium (ethanol, butanol) was mixed with The metal silicon powder and sintering aid were mixed for 35 hours using a mill. The mass ratio of the silicon content to the sintering aid content was adjusted to 0.89:0.11. Then, the mixture is added with a dispersion medium (ethanol, methyl ethyl ketone), an organic binder (acrylic acid, etc.), and The slurries were then made by adding the acrylic resin and plasticizer and remixing. The prepared slurry is removed from the ball mill and transferred to a defoamer, after which the slurry is defoamed by vacuum. The viscosity of the mixture is adjusted and the mixture is molded into a sheet of 100 x 100 x t0.38 mm. The doctor blade method was used for sheet forming.
[0052] Then, a ceramic slurry made of boron nitride is applied to the sheet body to form a thick A 10 μm thick layer of the release agent was formed on the surface of the sheet molded body, and then the sheet molded body was The degreasing treatment was carried out at 550°C in an oxidizing atmosphere.
[0053] Next, a sheet molded body having a separating agent layer made of boron nitride formed on its main surface was subjected to nitrogen partial pressure. The material was subjected to nitriding treatment at 1400° C. for 2 hours in a nitrogen-containing atmosphere of 0.2 MPa. Furthermore, the mixture was sintered at 1820°C for 9 hours in a nitrogen-containing atmosphere with a nitrogen partial pressure of 0.7 MPa. Thus, the silicon nitride substrate of Example 1 was produced.
[0054] Example 2 The mass ratio of the metal silicon powder and sintering aids after sintering to the silicon nitride content and sintering aid content is 0. The ratio of the adhesive strength was adjusted to 0.895:0.105, and a 20 μm thick adhesive was applied to the surface of the sheet. The layer was formed, and the sheet molding was subjected to a degreasing treatment in that state. A silicon nitride substrate of Example 2 was produced under the same production conditions as in Example 1.
[0055] Example 3 The mass ratio of the metal silicon powder and sintering aids after sintering to the silicon nitride content and sintering aid content is 0. The ratio of the adhesive strength was adjusted to 0.878:0.122, and a 25 μm thick adhesive was applied to the surface of the sheet. The layer was formed, and the sheet molding was subjected to a degreasing treatment in that state. A silicon nitride substrate of Example 3 was produced under the same production conditions as in Example 1.
[0056] Example 4 The mass ratio of the metal silicon powder and sintering aids after sintering to the silicon nitride content and sintering aid content is 0. The ratio of the adhesive strength was adjusted to 0.885:0.115, and a 35 μm thick adhesive was applied to the surface of the sheet. The layer was formed, and the sheet molding was subjected to a degreasing treatment in that state. A silicon nitride substrate of Example 4 was produced under the same production conditions as in Example 1.
[0057] Example 5 The mass ratio of the metal silicon powder and sintering aids after sintering to the silicon nitride content and sintering aid content is 0. The ratio of the adhesive strength was adjusted to 0.883:0.117, and a 35 μm thick adhesive was applied to the surface of the sheet. The layer was formed, and the sheet molding was subjected to a degreasing treatment in that state. A silicon nitride substrate of Example 5 was produced under the same production conditions as in Example 1.
[0058] Example 6 The mass ratio of the metal silicon powder and sintering aids after sintering to the silicon nitride content and sintering aid content is 0. The ratio of the adhesive strength was adjusted to 0.885:0.115, and a 50 μm thick adhesive was applied to the surface of the sheet. The layer was formed, and the sheet molding was subjected to a degreasing treatment in that state. A silicon nitride substrate of Example 6 was produced under the same production conditions as in Example 1.
[0059] ( reference Example 7) The same manufacturing conditions as in Example 1 were followed, except that the sheet compact was degreased without a release agent layer on its surface, and the sheet compact was sintered without a weight plate. reference The silicon nitride substrate of Example 7 was prepared.
[0060] Example 8 A porous plate with a porosity of 40% is formed on the surface of the sheet molded body in place of the separating agent layer. The same preparation conditions as in Example 1 were used except that the sheet molding was degreased in step 2. Thus, the silicon nitride substrate of Example 8 was produced.
[0061] Example 9 A semi-dense plate with a porosity of 15% is formed on the surface of the sheet molded body instead of the release agent layer. The manufacturing conditions were the same as in Example 1, except that the sheet molding was degreased in the same state. Thus, the silicon nitride substrate of Example 8 was produced.
[0062] ( reference Example 10) The metal Si powder and the sintering aid were adjusted so that the mass ratio of the silicon nitride content to the sintering aid content after sintering was 0.921:0.079, a sheet molded body of 240 x 180 x t0.29 mm was produced, a release agent layer of 20 μm in thickness was formed on the surface of the sheet molded body, and in this state, the sheet molded body was subjected to a degreasing treatment and sintered at 1840 ° C. for 12 hours in a nitrogen-containing atmosphere with a nitrogen partial pressure of 0.7 MPa. Except for this, the same production conditions as in Example 1 were followed. reference The silicon nitride substrate of Example 10 was prepared.
[0063] ( reference Example 11) The metal silicon powder and sintering aid were adjusted so that the mass ratio of silicon nitride content to sintering aid content after sintering was 0.92:0.08, and sintering was performed at 1830°C for 12 hours in a nitrogen-containing atmosphere with a nitrogen partial pressure of 0.7 MPa. reference According to the same preparation conditions as in Example 10 reference The silicon nitride substrate of Example 11 was prepared.
[0064] ( reference Example 12) The metal silicon powder and the sintering aid were adjusted so that the mass ratio of the silicon nitride content to the sintering aid content after sintering was 0.926:0.074, and a sheet molded body of 240 x 180 x t0.38 mm was produced. A release agent layer of 10 μm in thickness was formed on the surface of the sheet molded body, and the sheet molded body was subjected to a degreasing treatment in this state. reference According to the same preparation conditions as in Example 11, reference The silicon nitride substrate of Example 12 was prepared.
[0065] ( reference Example 13) The metal silicon powder and the sintering aid were adjusted so that the mass ratio of the silicon nitride content to the sintering aid content after sintering was 0.927:0.073, a release agent layer having a thickness of 20 μm was formed on the surface of the sheet molded body, and the sheet molded body was subjected to a degreasing treatment in this state. reference According to the same preparation conditions as in Example 12, reference The silicon nitride substrate of Example 13 was prepared.
[0066] (Comparative Example)
[0067] Comparative Example 1 Silicon nitride content and sintering aid content after sintering of metal Si powder, silicon nitride powder, and sintering aid The mass ratio was adjusted to 0.909:0.091, and the dimensions were 100 x 100 x t0.38m A sheet molded body having a thickness of 35 μm was produced, and a release agent layer having a thickness of 35 μm was formed on the surface of the sheet molded body. In this state, the sheet compact is subjected to a degreasing treatment, and then immersed in nitrogen at a nitrogen partial pressure of 0.7 MPa. The mixture was sintered in a nitrogen-containing atmosphere at 1820°C for 9 hours to produce a silicon nitride substrate. A silicon nitride substrate of Comparative Example 1 was produced under the same production conditions as those of Example 1 except for the above.
[0068] Comparative Example 2 Silicon nitride content and sintering aid content after sintering of metal Si powder, silicon nitride powder, and sintering aid The mass ratio was adjusted to 0.904:0.096, but the same preparation as in Comparative Example 1 was performed. A silicon nitride substrate of Comparative Example 2 was produced according to the conditions.
[0069] (Evaluation method) The characteristics of the silicon nitride substrates of the examples and comparative examples were evaluated as follows.
[0070] (Degree of orientation based on X-ray diffraction peak intensity) X-ray diffraction was performed using Cu-Kα radiation excited at 40 kV and 15 mA using the θ-2θ method. The scans were measured with a step size of 0.01°.
[0071] (Elemental analysis) Quantitative analysis of Si, N, Mg and rare earth elements was performed using a Rigaku ZSX Primu The analysis was performed by fluorescent X-ray analysis using sII. Inert gas fusion using MGA-920 - non-dispersive infrared absorption (NDIR) method The SiN content was calculated from the amount and ratio of Si and N, and the amount and ratio of Mg and O were calculated. The amount of sintering aid was calculated from the amount and amount ratio of rare earth element and O.
[0072] (Thermal Conductivity) Thermal diffusivity was measured by the flash method using a NETZSCH LFA 467 Hyp The experiment was carried out using a erFlash device. By irradiating the sample with flash light, the AC temperature response is measured with an IR detector, and the The thermal diffusivity was calculated from the attenuation rate for the amplitude and position. The surface of the specimen was blackened before the measurements were carried out.
[0073] (density measurement) The density was measured by the Archimedes method.
[0074] (Three-point bending strength) The three-point bending strength is measured using a 4mm x 35mm test piece according to JIS R1601:2008 According to the above, at room temperature (25℃), the distance between the two supports is 30 mm, and the distance from the midpoint of the two supports is The three-point bending strength was measured when the specimen was bent, and the average value of the three-point bending strengths of 10 specimens was calculated. .
[0075] Table 1 shows some of the conditions for producing the silicon nitride substrates in each example and each comparative example, as well as the evaluation results. The results are presented in summary.
[0076] [Table 1]
[0077] Examples 1 to 5, 10 to 13 in which a separating agent layer was formed on one main surface of a sheet body and a porous plate In the examples 6 to 9 formed, the β oriented in the thickness direction of the silicon nitride substrate was - The degree of orientation fa, which indicates the ratio of Si3N4 particles, is in the range of 0 to 0.3, and the thermal conductivity in the thickness direction is The conductivity was found to be over 80 W / m·K. [Explanation of symbols]
[0078] 10 Silicon nitride substrate 11 Silicon nitride particles 12 Grain boundary phase
Claims
1. When the substrate surface was irradiated with X-rays, β-Si 3 N 4 having an X-ray diffraction peak of β-Si oriented in the thickness direction in silicon nitride substrate 3 N 4 A silicon nitride substrate in which the degree of orientation fa, which indicates the ratio of the long axis (c-axis) of the grains, is in the range of 0.0144 to 0.2202, the average three-point bending strength of ten test pieces of 4 mm x 35 mm, when the test pieces are bent from the midpoint between two supports with a distance of 30 mm between the two supports, is in the range of 806 to 872 MPa, and the thermal conductivity in the thickness direction is in the range of 80 to 93.0 W / m K.
2. The silicon nitride substrate according to claim 1, Contains rare earth oxides and magnesium compounds as sintering aids Silicon nitride substrate.
3. The silicon nitride substrate according to claim 1 or 2, The size of the main surface is 400 to 40,000 mm 2 , the density is 3.15 to 3.40 g / cm 3 , and the dielectric strength is 20 kV / mm or more. Silicon nitride substrate.
Citation Information
Patent Citations
Silicon nitride base ceramics and manufacture
JP1988233078A
Siliceous nitride sintered compact having high thermal conductivity, its production and insulating base made of siliceous nitride sintered compact
JP1997030866A
Highly oriented silicon nitride sintered compact and production of the same
JP1998245270A
Silicon nitride ceramic substrate and silicon nitride ceramic circuit substrate using it and its manufacturing method
JP2002201075A
High-thermal conductive silicon nitride ceramic having high reliability and method of manufacturing the same
JP2007197226A